2021
DOI: 10.1021/acs.jpcc.1c01069
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Lithium with a Monolayer of Graphene Monoxide

Abstract: The interaction of Li atoms with a graphene monoxide (GmO) monolayer in various Li x C y O y structures is investigated to determine if a monolayer of GmO can bind Li atoms and to predict the maximum theoretical capacity of this potentially new anode material for Li-ion batteries. Density functional calculations show that Li atoms are adsorbed on the GmO monolayer by attaching to the oxygen atoms and that Li atoms tend to repel during lithiation. An isolated Li atom prefers adsorption at the hollow site of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…36,44 These covalent Li−O bonds are also shown to facilitate the Li + ions formation when leaving the graphene monoxide layer, which could be of substantial 27 benefit for fast charging Li batteries. 36 Li adsorption on GO layer is significantly stronger than its adsorption on the graphene layer due to stronger Li−O bond when compared to Li−C bond 44 and the coexistence of these bonds can further strengthen the GO-Li bond at the interface. Our DFT calculations further illustrate strong affinity of the Li ion to the oxygen-containing groups of the GO layer, which is favored by -1.83 eV.…”
Section: Energy Advances Accepted Manuscriptmentioning
confidence: 99%
See 3 more Smart Citations
“…36,44 These covalent Li−O bonds are also shown to facilitate the Li + ions formation when leaving the graphene monoxide layer, which could be of substantial 27 benefit for fast charging Li batteries. 36 Li adsorption on GO layer is significantly stronger than its adsorption on the graphene layer due to stronger Li−O bond when compared to Li−C bond 44 and the coexistence of these bonds can further strengthen the GO-Li bond at the interface. Our DFT calculations further illustrate strong affinity of the Li ion to the oxygen-containing groups of the GO layer, which is favored by -1.83 eV.…”
Section: Energy Advances Accepted Manuscriptmentioning
confidence: 99%
“…It is known that the confinement effect of 2D materials can arise from several synergistic factors such as (1) strong molecular interactions (e.g. van der Waals or covalent bonding) between 2D material and substrate leading to elevated pressures at the nanoscale interface; [36][37][38][39][40][41][42] (2) high mobility of ions on the surface of 2D materials; 36,41,43,44 and (3) high surface area of 2D materials for nucleation and growth of metals. 39,40,42,43 Al Balushi et al 37 reported synthesis of 2D gallium nitride through a migration-enhanced encapsulated growth technique by using epitaxial graphene.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…We should also mention that the structure is different from αand β-graphene monoxide phases predicted recently. 13 Carbon sheets of these phases consist of sp 3 -hybridized carbon atoms, connected by double bridges of oxygen atoms and they are dielectric. On the other hand, our structure (which we name γ-graphene monoxide) is totally sp 3 bonded, but is metallic.…”
mentioning
confidence: 99%